Addressing the Relationship between Area-based Management Tools (ABMTs) Including Marine Protected Areas (MPAs) and the Right of the Adjacent Coastal State to the High Seas: Recent Discussion and Suggestion - Firdos Firdos; Ubbadul Adzkiya’ (Jurnal Iqtisad, 2020)
Abstract Marine biodiversity beyond areas national jurisdiction (BBNJ) are characterized by high diversity of life and ecosystem and played central role in maintaining and supporting life on earth. Nevertheless, in recent times a number of factors have increasingly brought about considerable damage, at an increasing pace, to the marine ecosystem and biodiversity. And currently there are no specific rules governing this marine environment on the BBNJ. Therefore, in 2004 The United Nation General Assembly (UNGA) created the Ad Hoc Open-ended Informal Working Group to study issues relating to the conservation and sustainable use of BBNJ. With the process initiated by UNGA Resolution 69/292 of 19 June 2015, the General Assembly decided to develop an international legally binding instrument (ILBI) under the United Nations Convention on the Law of the Sea on conservation and sustainable use of BBNJ. The paper contains the current discussion on the development of the new international legally binding instrument (ILBI) for conservation and sustainable use of BBNJ. It discusses on going mechanisms to address issues related to the package agreed in 2011, specifically on the measures such as area-based management tools (ABMTs), including marine protected areas (MPAs). More specifically,this paper discusses on the relationship between instrument and the rights of coastal States over all areas under their jurisdiction, including continental shelf within and beyond 200 nautical miles and the exclusive economic zone. The paper concludes that there is a need for further cooperation and coordination in developing and implementing ABMTs including MPAs under new ILBI with the right of the coastal states over all areas under their jurisdiction. The paper also addressing the concept of due regard, adjacency, compatibility, and the right of the coastal state. This four concept can be used for the basic guideline in relationship between ABMTs including MPAs with costal States adjacent to the area beyond national jurisdiction (ABNJ).